Methotrexate modulates the kinetics of adenosine in humans in vivo. Issue 4 (24th November 2005) - Riksen, N P; Barrera, P; van den Broek, P H H; van Riel, P L C M; Smits, P; Rongen, G A
Abstract : Background: Animal studies suggest that the anti-inflammatory effect of methotrexate (MTX) is mediated by increased adenosine concentrations. Objective: To assess the effect of MTX on the vasodilator effects of adenosine and the nucleoside uptake inhibitor, dipyridamole, in humans in vivo as a marker for changes in adenosine kinetics. Methods: Ten patients with active arthritis were treated with MTX (15 mg/week). Measurements were performed before and after 12 weeks of treatment. At these time points, the activity of adenosine deaminase was measured in isolated lymphocytes, and forearm blood flow (FBF) was determined by venous occlusion plethysmography during administration of adenosine and dipyridamole into the brachial artery. Results: The Vmax of adenosine deaminase in lymphocytes was reduced by MTX treatment (p < 0.05). MTX significantly enhanced vasodilator response to adenosine (0.5 and 1.5 μg/min/dl of forearm tissue; mean (SE) FBF ratio increased from 1.2 (0.2) to 1.4 (0.2) and 2.2 (0.2) ml/dl/min, respectively, before and from 1.3 (0.1) to 1.8 (0.2) and 3.2 (0.5) ml/dl/min during MTX treatment; p<0.05). Also, dipyridamole-induced vasodilatation (30 and 100 μg/min/dl) was enhanced by MTX (FBF ratio increased from 1.2 (0.2) to 1.5 (0.3) and 1.8 (0.2), respectively, before and from 1.3 (0.1) to 1.8 (0.2) and 2.4 (0.4) during MTX treatment; p<0.05). Conclusions: MTX treatment inhibits deamination of adenosine and potentiates adenosine-induced vasodilatation. Also dipyridamole-induced vasodilatation is enhanced by MTX treatment, suggesting an increased extracellular formation of adenosine. These effects on the adenosine kinetics in humans may contribute to the therapeutic efficacy of MTX.